Outcome of pregnancy in underweight women after spontaneous and induced ovulation. Issue 6627 (2nd April 1988) - van der Spuy, Z M; Steer, P J; McCusker, M; Steele, S J; Jacobs, H S
Abstract : Low maternal weight before pregnancy and poor weight gain during pregnancy are known to result in an increased prevalence of low birthweight infants. Low body weight is also an important cause of amenorrhoea. The hypothesis that amenorrhoeic underweight women who become pregnant after induction of ovulation are more at risk of delivering low birthweight infants than underweight women who ovulate spontaneously was investigated. Forty one pregnant women in whom ovulation had been induced and 1212 in whom ovulation was spontaneous were studied. Women ovulating spontaneously whose weight was normal and who showed good weight gain during pregnancy (>450 g a week) had the lowest incidence (6%) of babies who were small for gestational age. Underweight women (body mass index <19·1) who ovulated spontaneously had a threefold increased risk of delivering babies who were small for gestational age (18%). Overall, the women in whom ovulation had been induced had an even higher risk of babies who were small for dates (25%), and this risk was greatest (54%) in those who were underweight. The outcome of pregnancy is related to weight before conception, which in many cases reflects nutritional state; lack of spontaneous ovulation indicates an increased risk of producing a small for dates infant. The most suitable treatment for infertility secondary to weight related amenorrhoea is therefore dietary rather than induction of ovulation.